Peran Siklus Hidup dan Bio Akuntansi Terhadap Produksi Ayam Broiler yang Berkelanjutan dengan Kecerdasan Lingkungan sebagai Variabel Moderasi - Hardianto, Ade Manggala; Novitasari, Yuli; Dade Suparna; Faujiah, Faujiah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the role of life cycle and bio-accounting in achieving sustainable broiler chicken production and to analyze whether environmental intelligence moderates these relationships. The life cycle approach is viewed as a comprehensive method for assessing resource efficiency, waste management, and environmental impacts throughout each stage of broiler production. Bio-accounting serves as a tool to measure and record biological aspects affecting livestock performance, feed consumption, emissions, and production efficiency. A quantitative method was employed through surveys distributed to small- and medium-scale broiler farmers. The results indicate that both life cycle and bio-accounting have a positive and significant effect on sustainable broiler production. Moreover, smart environmental strengthens these effects, as farmers with higher levels of environmental intelligence are better able to utilize bio-accounting information and life cycle assessments to manage resources efficiently and reduce environmental impacts. These findings highlight the importance of integrating life cycle analysis, bio-accounting practices, and environmental intelligence to enhance the sustainability of broiler production.